A morál kérdése Schiller színházában - Arató, Réka (Kultúratudományi Szemle, 2023)
The relationship between morality and theater comes up again and again in contemporary discussions. One of the most important dramatists, Friedrich Schiller, centred on the presentation of this relationship, which was a question and a task for him as well. In the 18th century, regarding the perception of the theatre’s morally enhancing effect, different views and many debates arose among the great thinkers of the time. Friedrich Schiller also takes a strong position in this discourse, especially with his opinion expressed in his essay, The Theater considered as a Moral Institution. In this study, I try to present the interesting details of Schiller’s writing, the antecedents and the influences that shaped Schiller's thinking.